Economics by design : - Collinge, Robert A. (Prentice Hall, 1997)
Current issues and main principles of economics are presented in this best-selling book; its easy readability and intuitive manner captures and holds readers' interest. It takes readers on an economic journey where they can explore theory and concepts, promoting economic reasoning and balanced thought. Real-world examples show readers how economics is around them everyday. A great wealth of topics is presented; coverage, although brief, is thorough. These topics include: the economic perspective; production and trade; demand and supply; pricing power; market power; earnings and income distribution; public goods, regulation, and information; public choice; output, employment, and the price level; money and monetary policy; and the global economy. An excellent read for all fledgling economists; this book can also serve as an excellent desk reference for professional economists and others in the field.